Three-Dimensional Porous Artemia Cyst Shell Biochar-Supported Iron Oxide Nanoparticles for Efficient Removal of Chromium from Wastewater - Yu Gao; Ying Liu; Xu Zhao; Xinchao Liu; Qina Sun; Tifeng Jiao (Molecules)
Chromium-containing wastewater poses severe threats to ecosystems and human health due to the high toxicity of hexavalent chromium (Cr(VI)). Although iron oxide nanoparticles (IONPs) show promise for Cr(VI) removal, their practical application is hindered by challenges in recovery and reuse. Herein, a novel three-dimensional porous nanocomposite, Artemia cyst shell biochar-supported iron oxide nanoparticles (ACSC@ IONP), was synthesized via synchronous pyrolysis of Fe3+-impregnated Artemia cyst shells (ACSs) and in situ reduction of iron. The optimized composite C@Fe-3, prepared with 1 mol/L Fe3+ and pyrolyzed at 450 °C for 5 h, exhibited rapid removal equilibrium within 5–10 min for both Cr(VI) and total chromium (Cr(total)), attributed to synergistic reduction of Cr(VI) to Cr(III) and adsorption of Cr(VI) and Cr(III). The maximum Cr(total) adsorption capacity was 110.1 mg/g at pH 2, as determined by the Sips isothermal model for heterogeneous adsorption. Competitive experiments demonstrated robust selectivity for Cr(VI) removal even under a 64-fold excess of competing anions, with an interference order of SO42− > NO3− > Cl−. Remarkably, C@Fe-3 retained 65% Cr(VI) removal efficiency after four adsorption–desorption cycles. This study provides a scalable and eco-friendly strategy for fabricating reusable adsorbents with dual functionality for chromium remediation.